Position of lingual foramina in cone beam computed tomography and its implications for choosing the dimensions of dental implants for mandibular symphysis - Pâmela Gomes SILVA; Isabel Cristina Gonçalves LEITE; Rodrigo Furtado de CARVALHO; Karina Lopes DEVITO; Marcos Vinícius Queiroz de PAULA; Matheus Furtado de CARVALHO (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Objective: To identify the lingual foramina in a Brazilian population of 210 individuals through Cone-Beam Computed Tomography images, in order to guide the installation of dental implants in the region of the mental symphysis. Methods: After identifying the lingual foramina on a parasagittal section, four measurements were taken: distance to the alveolar ridge, distance to the mandibular lower border, distance to the limit of the vestibular cortical, and alveolar ridge inclination angle. The measurements were compared in relation to gender by the Mann-Whitney test. The association between gender and the number of foramina was done by the chi-square test. Pearson's correlation analyzed the linear relationship between age and number of foramina. Results: Lingual foramina are present in 99.6% of the research participants. In the upper-inferior direction, a mean distance to the alveolar ridge of 21.4 mm was noted, while the mean distance to the lower mandibular border was 13.1 mm. In the bucco-lingual direction, a mean distance from the lingual foramina to the vestibular cortical of 15.2 mm is noted. The inclination angle of the alveolar ridge had a mean of 25.4º. Regarding gender, the test was not significant only for the distance to the vestibular cortical. Conclusion: The lingual foramina had a descending way in 100% of cases, being positioned mainly in the middle thirds (66.5%) and lower thirds (32.7%) of the mandibular ridge height. The use of dental implants up to 13 mm in length and up to 4 mm in diameter in the region of the symphysis mentualis is recommended.